Improving linkage to HIV care following a reactive HIV self-testing result among men in KwaZulu-Natal, South Africa - Mbuzeleni Hlongwa; Edward Nicol (BMC, 2024)
Abstract Background Despite the many interventions that have been implemented in sub-Saharan Africa to improve the uptake of HIV testing and antiretroviral (ART) initiation services, the rates at which men are tested for HIV and initiated on ART have remained consistently lower compared to those for women. We aim to investigate barriers and facilitators for linkage to care following HIVST positive results among men aged between 18 and 49 years, and use these findings to design an intervention to improve linkage to care among men in a high-HIV prevalent district in KwaZulu-Natal province, South Africa. Methods This multi-method study will be conducted over 24 months in eight purposively selected HIV testing and treatment facilities from December 2023 to November 2025. For the quantitative component, a sample of 197 HIV positive men aged 18-49 years old who link to care after HIV self-test (HIVST) will be recruited into the study. HIVST kits will be distributed to a minimum of 3000 men attending community services through mobile clinics that are supported by the Health Systems Trust, at different service delivery points, including schools, taxi ranks and other hotspots. The qualitative component will consist of in-depth interviews (IDIs) with 15 HIVST users and IDIs with 15 key informants. To design and develop acceptable, feasible, effective, and sustainable models for improving linkage to care, three groups of HIVST users (2*positive (N = 12) and 1*negative (N = 12)) will be purposively select to participate in a design workshop. Chi square tests will be used to identify social and demographic factors associated with linkage, while logistic regression will be used to identify independent factors. Kaplan Meier curves and cox proportional hazard models will be used to identify factors associated with time to event. Content and thematic approaches will be used to analyze the qualitative data. Discussion There remains an urgent need for designing and implementing innovative intervention strategies that are convenient and tailored for addressing the needs of men for improving HIV testing and linkage to care at early stages in resource-limited settings, to improve individual health outcomes, reduce transmission from HIV and minimize HIV-related mortality rates. Our proposed study offers several important innovations aimed at improving linkage to care among men. Our study targets men, as they lag the HIV continuum but are also under-researched in public health studies.